Cork suberin as an additive in offset lithographic printing inks (Industrial Crops and Products, 2000)
Suberin oligomers, isolated from cork (Quercus suber L.), were used as additives in ‘Waterless’ and vegetable-oil ink formulations, in the range of 2–10% w:w. The rheological behaviour of the suberin oligomers as well as of the inks, with and without suberin, were investigated as a function of temperature. It was shown that the addition of suberin induces a decrease of viscosity of both inks. The tack of pristine inks, suberin oligomers and their mixtures were determined at different temperatures: the variation of this parameter as a function of time provided information about the drying kinetics of these formulations. The tack of the ‘Waterless’ ink was found to increase with the introduction of suberin, whereas that of vegetable-oil based counterparts decreased. All the trends observed were interpreted in terms of the differences in composition between the two types of inks. Preliminary printing tests were carried out with the various suberin-containing inks

Comparative Analysis of the Lignins of Cork from Quercus suber L. and Wood from Eucalyptus globulus L. by Dry Hydrogen Iodide Cleavage (Lignin: Historical, Biological, and Materials Perspectives, 1999)
Lignin from cork (Quercus suber L.) was isolated by two procedures: organosolv extraction and dioxane-water (9:1) extraction in presence of HCl. These lignins were characterized using a mild hydrogen iodide-cleavage method followed by 1H NMR and GPC analysis. The results were compared with those for eucalyptus lignins (Eucalyptus globulus) isolated by the same procedures. The method used provided syringyl/guaiacyl ratios for the linear parts of the macromolecules and the degrees of crosslinking. The prevalence of guaiacyl units was demonstrated for cork lignin. Syringyl units were found to be minor components and present mainly in the linear parts of macromolecules. p-Hydroxyphenyl units were mainly condensed. Cork lignin was found to be significantly more cross-linked than eucalyptus lignin.
doi:10.1021/bk-2000-0742.ch014

Urethanes and polyurethanes from suberin 2: synthesis and characterization (INDUSTRIAL CROPS AND PRODUCTS, 1999)
Polyurethanes based on suberin from cork of Quercus suber L. and conventional isocyanate monomers were prepared and fully characterized in terms of both structure (FTIR and H-1 NMR spectroscopy) and thermal properties (differential scanning calorimetry and thermogravimetric analysis). Two fractions were systematically isolated, namely (i) methylene-chloride soluble products, which corresponded to linear and branched macromolecules and (ii) methylene-chloride insoluble products, representing the crosslinked material. The structures of these polymers were regular and no appreciable side reactions were detected. DSC analyses provided information about the glass transition temperature of both fractions and this parameter was correlated with the stiffness of the isocyanate used. The TGA of these polyurethanes showed that they started to degrade at about 175 degrees C and that the residue at 400 degrees C was around 50%. The highest amounts of insoluble fractions, as well as the highest T-g,s, were reached when an initial \{[\}NCO]/\{[\}OH] of unity was used. (C) 1999 Elsevier Science B.V. All rights reserved.

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.

Cork suberin as a new source of chemicals: 2. Crystallinity, thermal and rheological properties (Bioresource technology, 1998)
Suberin samples, obtained by alkaline methanolysis from cork (Quercus suber L.), were submitted to various physical characterizations; DSC, TGA, optical microscopy, density and rheological properties. A sub- stantial proportion of these oligomers possessed a microcrystalline character with a melting range between 0 and 50°C. The amorphous part was liquid at room temperature and did not display a detectable glass transition upon cooling because of its wide molecular weight distribution. The viscous behaviour of suberin at room temperature was both plastic and thixotropic because of the structuring role of the micro- crystals

Suberin-based polyurethanes: Synthesis, characterization and kinetics of their formation (BIOMASS FOR ENERGY AND INDUSTRY, 1998)
The synthesis and characterization of novel family of polyurethanes prepared by the polycondensation of suberin from Quercus suber L. with aliphatic and aromatic isocyanates are reported. A preliminary kinetic study, conducted with the aim of establishing the reactivity of suberin with different mono-, di- and polyisocyanates, showed that the kinetics of these condensations followed the classical second-order behaviour up to conversion of about 90%. The reactivity of different isocyanates followed patterns that could be readily rationalized in terms of steric hindrance and electronic factors, associated with each specific structure. The investigation was then extended to the synthesis of the new polymers which were characterized by FTIR and NMR spectroscopy and DSC. These suberin-based polyurethanes were a mixture of linear, branched and crosslinked structures. The proportion of the latter (insoluble fraction) being the highest for thr syntheses carried out in stoichiometric conditions, viz. \{[\}NCO](o) = \{[\}OH](o). The Tg of these materials depended of the diisocyanates used and correlated with their structural stiffness.

Isolation and characterization of a lignin-like polymer of the cork of Quercus suber L. (HOLZFORSCHUNG, 1996)
A lignin-like polymer was successfully extracted from the cork of Quercus suber L. using an organosolv-based technique. This material was characterized by elemental analysis, functional group analysis, nitrobenzene oxidation followed by HPLC analysis of the oxidation products, FTIR and liquid C-13 NMR. The evidence thus obtained indicated that the extracted material was composed mainly of a lignin-like polymer covalently bound to residual aliphatic structures which are not present in common lignins and which have been assigned to suberin. The latter is likely to be attached to the oxygenated side chains of the phenolic polymer but bonding through the aromatic ring can also be envisaged. No residual carbohydrates were detected. The phenolic polymer, composed mainly of guaiacyl-type units and small amounts of syringyl-type units, had a low methoxy content and a high degree of condensation. This polymer showed the presence of a fraction containing C6Cn units with n < 3 or even n < 2.

Characterization of the cork surface by inverse gas chromatography (Journal of colloid and interface science, 1995)
Inverse gas chromatography (IGC) at infinite dilution has been used to study the surface properties of cork from Quercus suber. The dispersive component of its surface energy was determined at different temperatures using n-alkanes as probes, and a GDS value of 38+-1mJ.m-2 at 40ºC was obtained. The surface acid (A)/base(B) properties were also evaluated by using polar probes and the results indicate that cork has an amphoteric character, with a KA/KB=1.1. The advantages of IGC, compared with the technique of contact angle measurements in the characterization of the cork surface, are discussed